Second trimester termination of pregnancy at Chris Hani Baragwanath academic hospital - Baloyi, Stephen (My University, 2015)
Objectives: The main objective of this study was to characterise women who presented at Chris Hani Baragwanath Academic Hospital (CHBAH) between 12 and 20 weeks for termination of pregnancy (TOP). Secondary objectives were to determine time to abortion, compare sonar gestational age to gestational age by dates and reasons for late presentation. Method: This was a prospective cohort study of women over the age of 18 who were referred to CHBAH for second trimester TOP between August 2012 and May 2013. The exclusion criteria were pregnancies more advanced than 20 weeks gestation. Data was collected from the medical file and by interview. Demographics and reasons to terminate were extracted from the files. Outcome variables included bleeding, pain, and time to abortion. Results: One hundred and ninety one women (91.39%) aborted. The median age of women was 25.00 (IQR=21.00-31.00), range (18-43). Women older than 25 years were 33% less likely to abort than women less than 25 years of age. Ninety nine women (47.14%) bled severely. One woman had a uterine perforation following evacuation of the uterus. The median gestational age by sonar was14.71 (IQR=13.86-16.14), range (13.00-20.00). The median gestational age by dates was13.57 (IQR=12.29-15.00), range (4.14-26.28). One hundred and thirty five women (63.98%) had an MVA for RPOC using analgesia following medical induction. Two women (0.95%) needed hysterotomy following failed TOP. The median time to abortion was 11.50(IQR=8.67-17.92), range (3.50-69.33) and incidence rate of 0.5 per hour or 1 per 2hours. Conclusion: The majority of women (91%) aborted within 72 hours following medical induction with less complication rate and short induction to abortion time. This affirm misoprostol efficacy as the suitable drug for conducting second trimester medical TOP.
A Dissertation that is being submitted for an MMed in Obstetrics and Gynaecology in partial fulfilment of the FCOG (SA) Part II 07 April 2015
Keywords: Abortion, Induced; Hospitals; Gestational Age; Pregnant Women